2021
DOI: 10.1002/chem.202003224
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Isocyanide‐Based Reactions: Beyond Passerini and Ugi Multicomponent Reactions

Abstract: The development of catalytic enantioselective isocyanide‐based reactions is currently of great interest because the resulting products are valuable in organic synthesis, pharmacological chemistry, and materials science. This review assembles and comprehensively summarizes the recent achievements in this rapidly growing area according to the reaction types. Special attention is paid to the advantages, limitations, possible mechanisms, and synthetic applications of each reaction. In addition, a personal outlook … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 154 publications
(90 reference statements)
1
25
0
Order By: Relevance
“…Multicomponent reactions (MCRs) and associated one-pot synthesis such as domino, tandem and cascade reactions have always been one of the most signicant scopes in the development of new methodologies in organic synthesis and catalysis due to their great applications, particularly in pharmaceutical studies. [1][2][3][4] MCRs oen produce highly complex molecules from simple precursors, thus, avoiding complicated purication steps and saving solvents, reagents and times. [5][6][7] Spiro compounds show a broad range of effective performance in pharmacology.…”
Section: Introductionmentioning
confidence: 99%
“…Multicomponent reactions (MCRs) and associated one-pot synthesis such as domino, tandem and cascade reactions have always been one of the most signicant scopes in the development of new methodologies in organic synthesis and catalysis due to their great applications, particularly in pharmaceutical studies. [1][2][3][4] MCRs oen produce highly complex molecules from simple precursors, thus, avoiding complicated purication steps and saving solvents, reagents and times. [5][6][7] Spiro compounds show a broad range of effective performance in pharmacology.…”
Section: Introductionmentioning
confidence: 99%
“…The key results of extensive optimization of the reaction conditions are summarized in Table 1. Initially, we tested the use of Dixon‐type phosphine ligands [5c] L1 and L2 in combination with Ag 2 CO 3 , which have been successfully applied in [3+2] cycloaddition reactions of activated isocyanides, [4f] for our reaction. Gratifyingly, the formation of the desired product 3 aa was observed, albeit with moderate stereoselectivity (entries 1 and 2).…”
Section: Methodsmentioning
confidence: 99%
“…The crosslinking and functionalization of CMC was performed using Ugi/Passerini MCRs. [94][95][96][97] It was observed that the formation of carboxamide-skeletons during the crosslinking of CMC, enhanced the bioavailability of CMC multicomponent hydrogels. The hydrogel developed, exhibited a controlled delivery of gentamicin and showed antibacterial activity towards S. aureus and E. coli.…”
Section: Simultaneous Crosslinkingmentioning
confidence: 99%